Justice Delayed is Assimilation Denied: Rightwing Terror, Fear and Social Assimilation of Turkish Immigrants in Germany - Sumit S. Deole (Center for Economic Studies and ifo Institute (CESifo), 2018)
Using the German Socioeconomic Panel (SOEP) data, this paper offers the first evidence that the 2011 news revelations about crimes committed by National Socialist Underground (NSU) network in early the 2000s resulted in an increase in worries about xenophobic hostility among NSU's targeted groups. This serves as an indication of the minority's perceived maltreatment by German institutions while investigating the NSU crimes. The results further show that the revelations significantly reinforced a feeling of estrangement among Turks, who were now less likely to self-identify as Germans and more likely to see themselves as foreigners; they, therefore, tended to bond more strongly with the ethos of their country of origin. The results also demonstrate that Turks reported a substantial decrease in their health satisfaction and subjective wellbeing. In conclusion, the paper underlines the pertinence of judicial efficacy over rightwing crimes for assimilation and welfare of immigrants.
Keywords: D63; F22; J15; Z10; 330; rightwing crimes; immigration; delayed justice; social assimilation